Response to direct selection for grain yield under drought stress in rice - Venuprasad, R.; Lafitte, H.R.; Atlin, G.N. (Wiley, 2007)
Drought is a major cause of yield loss in rain‐fed rice (Oryza sativa L.), grown on over 40 million ha in Asia. The objective of this study was to evaluate the effectiveness of direct selection for yield under drought stress in upland rice in populations derived from crosses between irrigated high‐yielding cultivars and upland‐adapted cultivars. Random F2:4 lines from five populations were screened for grain yield in fully irrigated lowland fields under nonstress conditions and in uplands under severe reproductive‐stage drought stress. Stress caused mean yield reduction of 64% across populations. Broad‐sense heritability for yield was not consistently lower in stress than in nonstress trials. Response to selection was evaluated in two crosses in subsequent seasons. Stress‐selected lines had a yield advantage of 25 to 34% over random lines when evaluated at stress levels similar to those in which they were selected. Yield gains under very severe stress occurred only in a population derived from a highly tolerant parent. Direct selection usually gave greater response under stress than indirect selection under nonstress conditions. Direct selection under dry‐season stress also gave response under naturally occurring wet‐season stress. These results support the hypothesis that selection for yield under reproductive‐stage drought stress is effective in rice, and that choice of donor is very important in breeding drought‐tolerant rice.